Does Technology Matter?: literature Review Adopsi Teknologi Dalam Riset Ekonomi Keuangan Syariah - Wasyith Wasyith (Al-Urban: Jurnal Ekonomi Syariah dan Filantropi Islam, 2019)
Technology disruption brings us to a new era full of opportunities and challenges. In digital transformation, various cutting-edge innovations in the economy were born and developed. At this point, Islamic economics and finance can utilize the advantages provided by technological advances, such as features of generativity, convergence, and culture of democratization to promote ethical principles such as togetherness, justice, equality, and honesty. In the realm of research, if previously the issue of technology had not been enough of the attention of researchers, then the trends were slowly changing. This research tries to review the research on the theme of Islamic economics and finance with the emphasis on the use of the technology sector in it. This research is a literature review and uses a descriptive analysis of 28 English-language articles based on Google Scholar. The sample articles are those published from 2014 to 2019. The results showed that technology adoption has become a common concern of researchers in the field of Islamic economics and finance. The theme of developing technology-based Islamic economic and financial instruments in various sectors continues to emerge, from Islamic banking, Islamic finance, Islamic monetary systems, and zakat. Besides, this research also offers a framework on how to develop Islamic economic and financial research going forward.